(3cfR GdOQQ hLGeY GdZQQs - (3CHh HcQ Hf YHO Gddg Hf CjHc, GdeYQha HGHf GdOhGOGQqj (B( (3UGMH UQNO (B)(3,J (B736 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CWaC aCNP LeQI GdETQGc HeRf MjG OhdI GdCJQGc s
(3BNQgG (B:s
(3HPcQ GdSGOI GdaVdGA GdPjf COQcge HGdehdO heG GNJGQg ef fKQge hTYQge s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B66 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B65s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B218 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs